La inversión privada en el alojamiento turístico en el cantón Riobamba provincia de Chimborazo - Mery Jaritza, Quintanilla Vergara (2024)
ABSTRACT: This research deeply analyzes tourism factors related to private investment and tourist accommodation. In the first case, the economic contribution, fixed assets, and income were considered, and in the second case, the establishments, the lodging service, and complementary services. The Objective was to analyze the relationship between private investment and Tourist Accommodation in the Riobamba canton, province of Chimborazo, by contrasting the factors that belong to each of the variables under study. The Methodology was correlational and descriptive level. The contrast test with Spearman's correlation coefficient was used. The information was collected through surveys applied to a sample of 65 participants who were owners/managers of tourist accommodations in Riobamba. The two variables under study consisted of 3 dimensions, and each dimension had three indicators, which in total represent 18 questions. In addition, bibliographic sources related to the topic were consulted. The research results show that the applied questionnaire had high reliability in its internal consistency. The majority criteria surveyed agree that all the factors or indicators of the dimensions of the two variables are relevant, that is, the economic contribution, fixed assets, income, establishments, lodging services, and services. Complementary, they are key for private investment to increase the capacity of tourism, offering quality services and the continuous improvement of customer service in tourist accommodation. Spearman correlation coefficient (rs) shows a high correlation between economic contribution, fixed assets, and income from tourist accommodation. In conclusion, the capacity and quality of tourist accommodation depends on private investment. Key words: Tourism, private investment, tourist accommodation, financial contribution